PENGARUH PENERAPAN KLINIK PINTAR TERHADAP ANAK SLOW LEARNER DI MI BADRUSSALAM - Rahmah, Azizatur; Farisia, Hernik; Rizki Amaliyah, Nadia; Amaliatus Sholikha, Risma; Engrasia Febryantika, Arlynda; Husnah, Barizatul; Maulandini, Tristi (Jurusan Pendidikan Luar Biasa, 2023)
Children with slow learner characterized by a slow response in learning, completing assisgnmentlately, short-term memory, lower learning achievement, and low motivation. In academiccompetencies, children with slow learner category faced special needs in reading, writing, andother academic compulsory, etc. Therefore, a program as Klinik Pintar “Smart Program” wasimplemented at Badrussalam Islamic Primary School in Surabaya. This study aims to reveal theimplementation of klinik pintar in developing students’ academic capability with slow learner.This research used qualitative design with Miles and Huberman as the analyses technique. Theresults revealed that 2 children at Badrussalam Islamic primary school have been identified aschildren with special needs as slow learners. To accommodate their needs, the schoolimplemented smart clinic program that focused on developing students’ ability in reading andwriting. The activity conducted in this program implemented by considering students academicdifferentiation started from learning alphabet, words, and sentences. In improving writingcompetencies, students also learned how to use pencils, sitting position in learning, and doingexercise in writing to optimize students’ motoric skill.Keyword: Smart Clinic, Slow Learner, Academic Ability